Molecular mechanisms of COVID-19-induced pulmonary fibrosis and epithelial-mesenchymal transition - Pi, Peng; Zeng, Zhipeng; Zeng, Liqing; Han, Bing; Bai, Xizhe; Xu, Shousheng (Frontiers in Pharmacology, 2023)
As the outbreak of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) first broke out in Hubei Province, China, at the end of 2019. It has brought great challenges and harms to global public health. SARS-CoV-2 mainly affects the lungs and is mainly manifested as pulmonary disease. However, one of the biggest crises arises from the emergence of COVID-19induced fibrosis. At present, there are still many questions about how COVID-19 induced pulmonary fibrosis (PF) occurs and how to treat and regulate its long-term effects. In addition, as an important process of fibrosis, the effect of COVID-19 on epithelial-mesenchymal transition (EMT) may be an important factor driving PF. This review summarizes the main pathogenesis and treatment mechanisms of COVID-19 related to PF. Starting with the basic mechanisms of PF, such as EMT, transforming growth factor-β (TGF-β), fibroblasts and myofibroblasts, inflammation, macrophages, innate lymphoid cells, matrix metalloproteinases and tissue inhibitors of metalloproteinases, hedgehog pathway as well as Notch signaling. Further, we highlight the importance of COVID-19induced EMT in the process of PF and provide an overview of the related molecular mechanisms, which will facilitate future research to propose new clinical therapeutic solutions for the treatment of COVID-19-induced PF.